Can Carbon Trading Policy Promote China’s Decoupling of Carbon Emission From the Perspective of Technology-Driven Innovation? - Lyu, Bai; Ni, Wenli; Ostic, Dragana; Yu, HuaChen; Qureshi, Naveed Akhtar (Frontiers in Environmental Science, 2022)
The emissions trading policy is considered a key measure for China to achieve its “double carbon” goal. In this paper, two types of Tapio carbon decoupling models are constructed, panel data for 30 provinces and cities in China from 2004 to 2017 are selected, and the difference-in-differences (DID) model is used to evaluate the role of carbon trading policies on carbon decoupling. The study shows that carbon emissions trading policies can significantly promote carbon decoupling in China and that the formulation and implementation of such environmental regulations promote carbon decoupling with the help of two intermediary variables: gray technology innovation; and clean technology innovation. Based on the findings, it is concluded that China should actively build a unified national carbon trading market, ensure the synergistic coupling of emission reduction targets and economic growth targets, and effectively play the role of the carbon trading market in inducing and promoting low-carbon technology innovation to help decouple carbon.